Dampak Hukum Perkawinan Janda Tanpa Putusan Pengadilan Yang Berkekuatan Hukum Tetap - Sulkifli M. Akil; Fifiana Wisnaeni (Notarius, 2023)
AbstractMarriage is legal if it is carried out according to each other's beliefs and also recorded based on the laws and regulations and divorce can only be done before a court session. This paper aims to specify the legal consequences of widowed marriages without a court decision which had permanent legal force. This research uses the type of doctrinal research, namely research that emphasizes the legal conception seen as a set of laws and regulations that are arranged systematically based on the order with the characteristic of harmonization. The results reveals that: the legal consequences of widows' marriages without court decisions that had permanent legal force are a) legal consequences for the widow (wife), namely her marital status is invalid and has no legal relationship with her husband because it does not meet the requirements of marriage and is considered still bound by previous marriages. b) legal consequences for children, namely children born from a second marriage only have a legal relationship with the mother and her mother's family, c) legal consequences for assets, namely assets obtained from a second marriage are not joint assets.Keywords: legal consequences; marriage; widowAbstrakPerkawinan sah bila dijalankan berdasarkan kepercayaan masing-masing serta dicatat berdasarkan peraturan perundang-undangan dan perceraian hanya bisa dijalankan di hadapan sidang pengadilan. Tujuan dari penulisan adalah guna mengidentifikasi dampak hukum perkawinan janda tanpa putusan pengadilan yang berkekuatan hukum tetap. Penelitian menggunakan tipe penelitian doktrinal yakni penelitian yang memfokuskan kepada konsepsi hukum dilihat selaku seperangkat peraturan perundang-undangan yang tersusun sistematis menurut tata urutan dengan ciri khas berupa harmonisasi. Hasil penelitian memperlihatkan bahwasanya dampak hukum perkawinan janda tanpa putusan pengadilan yang berkekuatan hukum tetap ialah a) dampak hukum terhadap janda (istri) yakni status perkawinannya tidak sah serta tak mempunyai hubungan hukum dengan suaminya, dikarenakan tak memenuhi persyaratan perkawinan dan dianggap masih terikat perkawinan sebelumnya. b) dampak hukum terhadap anak yakni anak yang dilahirkan dari perkawinan kedua hanya memiliki hubungan hukum dengan ibu serta keluarga ibunya, c) dampak hukum terhadap harta yakni harta benda yang didapat dari perkawinan kedua bukan ialah harta bersama.Kata kunci: dampak hukum; perkawinan; janda